Cross-sectional survey study to examine underuse of twice daily inhaled maintenance therapy among patients with asthma. (2nd November 2019) - Stanford, Richard H.; Bell, Chris; Nag, Arpita; Johnson, Phaedra T.; Johnson, Michael P.; Watkins, Angela
Abstract: Objective: Anecdotal evidence suggests that some patients with asthma intentionally use their twice-daily (BID) inhaled controller therapy once daily (QD), thus not achieving optimal dosing levels. This study identified the prevalence of and factors associated with intentional QD use of BID-indicated controllers among adult patients with asthma. Methods: This was a cross-sectional survey study of adults using inhaled controllers intended for BID dosing for treatment of asthma and/or COPD. Survey responses were linked to administrative claims data for the prior 12 months (baseline). Results of patients indicating both an asthma diagnosis and current intentional QD or BID use of controllers are presented. Results: Of 1401 patients with asthma, 30.9% reported intentional QD use of their controller and 69.1% reported BID use. Intentional QD use was mostly a function of patients' lack of perceived need for BID treatment (44.1%) or physician orders to take their controller QD (34.0%). Patients reporting intentional QD use tended to be healthier (higher health status scores, and lower Charlson comorbidity scores, ambulatory and ER visits, and healthcare costs) with better asthma control (lower asthma-related ER and ambulatory visits and rescue medication use, and higher Asthma Control Test scores) compared with patients reporting BID use. Conclusions: Perceptions regarding health and the necessity of controller use to control or treat asthma were the main drivers of medication-taking behavior. Patients with less severe asthma were more likely to report once daily use of their inhaled controller, but still maintained asthma control.